2016
DOI: 10.1080/10826068.2015.1045615
|View full text |Cite
|
Sign up to set email alerts
|

Use of autochthonous lactic acid bacteria starters to ferment mango juice for promoting its probiotic roles

Abstract: Strains of Leuconostoc mesenteroides, Pediococcus pentosaceus, and Lactobacillus brevis were identified from mango fruits by partial 16S rDNA gene sequence. Based on the ability of producing mannitol and diacetyl, Leuconostoc mesenteroides MPL18 and MPL39 were selected within the lactic acid bacteria isolates, and used as mixed starters to ferment mango juice (MJ). Both the autochthonous strains grew well in fermented mango juice (FMJ) and remained viable at 9.81 log cfu mL(-1) during 30 days of storage at 4°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…Overall, the stationary growth phase was reached after 18 h fermentation at 37°C, when both the commercial and the autochthonous strains reached a cell density of 10.52 ± 0.37 Log CFU/mL (Figure 5A ). Based on previous research, we know that allochthonous strains tend to demonstrate poor growth characteristics in comparison with autochthonous isolates ( Di Cagno et al, 2009a ), as has been reported for fermented carrots (8.57/7.62 Log CFU/mL), French beans (8.95/8.08 Log CFU/mL), marrows (8.48/7.40 Log CFU/mL), mangoes (10.33/7.71 Log CFU/mL), and tomatoes (9.8/8.52 Log CFU/mL) ( Di Cagno et al, 2008 , 2009a , b ; Liao et al, 2016 ). Although almost a similar behavior was observed for the commercial species, the indigenous isolates may certainly have influenced the fermentation and the characteristics of the final product.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, the stationary growth phase was reached after 18 h fermentation at 37°C, when both the commercial and the autochthonous strains reached a cell density of 10.52 ± 0.37 Log CFU/mL (Figure 5A ). Based on previous research, we know that allochthonous strains tend to demonstrate poor growth characteristics in comparison with autochthonous isolates ( Di Cagno et al, 2009a ), as has been reported for fermented carrots (8.57/7.62 Log CFU/mL), French beans (8.95/8.08 Log CFU/mL), marrows (8.48/7.40 Log CFU/mL), mangoes (10.33/7.71 Log CFU/mL), and tomatoes (9.8/8.52 Log CFU/mL) ( Di Cagno et al, 2008 , 2009a , b ; Liao et al, 2016 ). Although almost a similar behavior was observed for the commercial species, the indigenous isolates may certainly have influenced the fermentation and the characteristics of the final product.…”
Section: Resultsmentioning
confidence: 94%
“…Researchers have explored the use of indigenous LAB strains isolated from food materials and their addition to more complex food systems, with the aim of improving the quality characteristics and functional properties of the end products ( Galvez et al, 2007 ; Di Cagno et al, 2009a ; Ong et al, 2012 ). For instance, autochthonous LAB obtained by the fermentation of mango juice can be employed to compensate for the loss of antioxidant substances, increase the contents of nutrients such as organic acids and mannitol, and provide better sensory characteristics such as acidity and sweetness ( Liao et al, 2016 ). However, different probiotics have different survival characteristics and functional performance in various juices.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic aroma is a significant sensorial feature of dairy products [ 33 , 44 ] chocolate [ 19 ], and even sourdough bread [ 38 ]. Strains of L. mesenteroides are diacetyl [ 8 , 45 ] and acetoin producers [ 19 ]. E. faecium strains are also considered helpful in cheese manufacturing due to the production of desirable flavors associated with citrate metabolism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum [ 2 , 3 , 4 , 5 ] currently referred to as Lactiplantibacillus plantarum comb. nov. [ 6 ], Leuconostoc pseudomesenteroides [ 3 , 7 ], Weissella confusa [ 3 , 4 ] and Leuconostoc mesenteroides [ 3 , 8 ] are counted among the LAB obtained from fresh fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the functional enzymes on the market to fruits, vegetables as raw materials, by adding a variety of beneficial bacteria produced by fermentation. They are rich in vitamins, minerals, bioactive components and biological enzymes of functional microbial fermentation products [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%